2007
DOI: 10.1124/jpet.106.117549
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide-Mediated CB1/CB2Cannabinoid Receptor-Independent Nitric Oxide Production in Rabbit Aortic Endothelial Cells

Abstract: We have previously shown that the endocannabinoid anandamide and its metabolically stable analog (R)-methanandamide produce vasorelaxation in rabbit aortic ring preparations in an endothelium-dependent manner that could not be mimicked by other CB 1 cannabinoid receptor agonists (Am J Physiol 282: H2046 -H2054, 2002). Here, we show that (R)-methanandamide and abnormal cannabidiol stimulated nitric oxide (NO) production in rabbit aortic endothelial cells (RAEC) in a dosedependent manner but that other CB 1 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 39 publications
3
47
0
Order By: Relevance
“…There are however, a number of potential targets that may be responsible. It has been reported that endogenous cannabinoids such as 2-AG and anandamide may induce vasodilation through a non-cannabinoid receptor (such as vanilloid receptor) present on endothelial cells (Golech et al, 2004, McCollum et al, 2007. It has been shown that cannabidiol, the nonpsychoactive constituent of cannabis, also reduced cerebral infarction due to increases in rCBF during ischemia, through activiation of the serotonergic 5-hydroxytryptamine 1A receptor (Mishima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are however, a number of potential targets that may be responsible. It has been reported that endogenous cannabinoids such as 2-AG and anandamide may induce vasodilation through a non-cannabinoid receptor (such as vanilloid receptor) present on endothelial cells (Golech et al, 2004, McCollum et al, 2007. It has been shown that cannabidiol, the nonpsychoactive constituent of cannabis, also reduced cerebral infarction due to increases in rCBF during ischemia, through activiation of the serotonergic 5-hydroxytryptamine 1A receptor (Mishima et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesis that modification of the endocannabinoid system could influence outcome following ischemia was based upon prior reports that this system can have direct effects on neuronal function and can also modify inflammatory responses (Baker et al, 2001, van der Stelt et al, 2001, Muthian et al, 2004, McCollum et al, 2007. Both of these actions could have significant impact on cerebral ischemia/reperfusion injury.…”
Section: Discussionmentioning
confidence: 99%
“…In animal studies, there is a large evidence supporting a role for ECS in improving endothelial function and nitric oxide production 37 as well as THC has been shown to Endothelial dysfunction in erectile dysfunction A Aversa et al improve endothelium-dependent relaxation. [38][39][40] In addition, the EC anandamide, improves neurogenic relaxation of corpus cavernosum in diabetic rats. 41 On the contrary, occasional myocardial infarction after acute assumption of cannabis has been reported in humans.…”
Section: Endothelial Dysfunction In Erectile Dysfunction a Aversa Et Almentioning
confidence: 99%
“…This observation indicated the existence of an endothelial non-CB1/non-CB2 receptor, which is now referred to as abn-cbd receptor, or endothelial anandamide receptor. The presence of such receptors was also confirmed in rabbit aortic ring preparations and rat aortic endothelial cells (143,154), as well as in rabbit pulmonary arterial strips (221). In the CNS, microglial abn-cbd receptors mediate neuroprotective effects (119) and regulate cell migration (247).…”
Section: Biosynthesis and Receptors Of Endocannabinoids In Cells Invomentioning
confidence: 74%